Expression of the metalloproteases MMP-1, MMP-2, MMP-3, MMP-9, MMP-11, TIMP-1 and TIMP-2 in angiocentric midfacial lymphomas - Roa Lourdes; Montes Adriana; Abarca Jorge; Betancourt Alejandro; Meneses-García Abelardo; Ruíz-Godoy Luz (World Journal of Surgical Oncology, 2008)
Abstract Background Extranodal T/NK cell lymphomas possess distinctive clinico-pathological characteristics: they are angiocentric, exhibit extensive necrosis. Prognosis is poor in the short term. The objective is to explore the expression of different MMPs in the cells and stroma which are around of the blood vessels damaged and their correlation with clinico-pathological parameters. Patients and methods Twenty cases of this type of lymphomas were studied and collected patient clinical data. The expressions of MMP-1, 2, 3, 9, 11, 13 and TIMP-1, 2 were studied by immunohistochemistry. Ultrastructural studies were performed in two cases. Statistical analysis was done with Fisher's exact test, Chi2 test. Results Of the 20 patients, 13 were men with median age of 43 years. In 13 patients the primary tumor was localized in the nasal cavity. Treatment was combined chemotherapy and radiotherapy in 60%. The 55% advanced clinical stages, 70% died from the disease. There were neoplastic cell and peritumoral fibroblasts positivity to MMP-1 and MMP-11 in most of the cases. The MMPs-2, 3 and 9 were expressed in neoplastic cell between 30 to 65%of the cases. TIMP-1 was presented mainly in the epithelium and TIMP-2 was poor expressed of the all cases. Conclusion There were no statistical significance between the different enzymes used and the clinical parameters, besides status and survival of the patients. It is necessary to study more enzymes and focus them to quantify and determine their activity, in order to have a better correlation with histological features in this type of neoplasm.